Identification of Potent Inhibitors of the Trypanosoma brucei Methionyl-tRNA Synthetase via High-Throughput Orthogonal Screening. (January 2015) - Pedró-Rosa, Laura; Buckner, Frederick S.; Ranade, Ranae M.; Eberhart, Christina; Madoux, Franck; Gillespie, J. Robert; Koh, Cho Yeow; Brown, Steven; Lohse, Jacqueline; Verlinde, Christophe L. M.; Fan, Erkang; Bannister, Thomas; et al.
Improved therapies for the treatment of Trypanosoma brucei, the etiological agent of the neglected tropical disease human African trypanosomiasis, are urgently needed. We targeted T. brucei methionyl-tRNA synthetase (MetRS), an aminoacyl-tRNA synthase (aaRS), which is considered an important drug target due to its role in protein synthesis, cell survival, and its significant differences in structure from its mammalian ortholog. Previous work using RNA interference of MetRS demonstrated growth inhibition of T. brucei, further validating it as an attractive target. We report the development and implementation of two orthogonal high-throughput screening assays to identify inhibitors of T. brucei MetRS. First, a chemiluminescence assay was implemented in a 1536-well plate format and used to monitor adenosine triphosphate depletion during the aminoacylation reaction. Hit confirmation then used a counterscreen in which adenosine monophosphate production was assessed using fluorescence polarization technology. In addition, a miniaturized cell viability assay was used to triage cytotoxic compounds. Finally, lower throughput assays involving whole parasite growth inhibition of both human and parasite MetRS were used to analyze compound selectivity and efficacy. The outcome of this high-throughput screening campaign has led to the discovery of 19 potent and selective T. brucei MetRS inhibitors.